Surveillance of pneumococcal diseases in Central and Eastern Europe. Issue 8 (2nd August 2016) - Ceyhan, Mehmet; Dagan, Ron; Sayiner, Abdullah; Chernyshova, Liudmyla; Dinleyici, Ener Çağrı; Hryniewicz, Waleria; Kulcsár, Andrea; Mad'arová, Lucia; Pazdiora, Petr; Sidorenko, Sergey; Streinu-Cercel, Anca; Tambić-Andrašević, Arjana; et al.
ABSTRACT: Pneumococcal infection is a major cause of morbidity and mortality worldwide. The burden of disease associated with S. pneumoniae is largely preventable through routine vaccination. Pneumococcal conjugate vaccines (e.g. PCV7, PCV13) provide protection from invasive pneumococcal disease as well as non-invasive infection (pneumonia, acute otitis media), and decrease vaccine-type nasopharyngeal colonisation, thus reducing transmission to unvaccinated individuals. PCVs have also been shown to reduce the incidence of antibiotic-resistant pneumococcal disease. Surveillance for pneumococcal disease is important to understand local epidemiology, serotype distribution and antibiotic resistance rates. Surveillance systems also help to inform policy development, including vaccine recommendations, and monitor the impact of pneumococcal vaccination. National pneumococcal surveillance systems exist in a number of countries in Central and Eastern Europe (such as Croatia, Czech Republic, Hungary, Poland, Romania and Slovakia), and some have introduced PCVs (Czech Republic, Hungary, Kazakhstan, Russia, Slovakia and Turkey). Those countries without established programs (such as Kazakhstan, Russia and Ukraine) may be able to learn from the experiences of those with national surveillance systems. The serotype distributions and impact of PCV13 on pediatric pneumococcal diseases are relatively similar in different parts of the world, suggesting that approaches to vaccination used elsewhere are also likely to be effective in Central and Eastern Europe. This article briefly reviews the epidemiology of pneumococcal disease, presents the latest surveillance data from Central and Eastern Europe, and discusses any similarities and differences in these data as well the potential implications for vaccination policies in the region.